Design of S–S bond containing maleimide-conjugated closo-dodecaborate (SSMID): identification of unique modification sites on albumin and investigation of intracellular uptake. Issue 22 (12th April 2019) - Ishii, Satomu; Sato, Shinichi; Asami, Hiroya; Hasegawa, Tomoko; Kohno, Jun-Ya; Nakamura, Hiroyuki
Abstract : The S–S bond containing maleimide-conjugated closo -dodecaborate (SSMID) was synthesised to identify the binding sites in bovin serum albumin (BSA). Abstract : An S–S bond containing maleimide-conjugated closo -dodecaborate (SSMID) was synthesised for identification of albumin binding sites. Three Lys residues, Lys221, Lys413 and Lys431, were identified as SSMID modification sites in addition to Cys34 in bovin serum albumin (BSA). Fluorescent-labelled MID-BSA was found to be accumulated in the cytosol of HeLa cells.